More severe comorbidities, advanced age, and incomplete vaccination increase the risk of COVID-19 mortality - Pradhevi, Lukita; Soegiarto, Gatot; Wulandari, Laksmi; Lusida, Michael AP.; Saefudin, Rendra P.; Vincent, Agustinus (Narra Sains Indonesia, 2024)
Numerous studies have stated that comorbidities are risk factors for coronavirus disease 2019 (COVID-19) mortality, but few have considered the severity or stage of these comorbidities. The aim of this study was to determine the association between the severity of comorbidity, age, and number of COVID-19 vaccinations with COVID-19 mortality. This case-control study was conducted from July 2021 until December 2022 at the Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. The patients were divided into non-survived patients (case group) and survived patients (control group). The inclusion criteria for cases were adult patients hospitalized with confirmed COVID-19, based on reverse transcriptase-polymerase chain reaction (RT-PCR) testing of nasopharyngeal swabs. Using total sampling, 1,046 confirmed COVID-19 patients, which consisted of 450 (43%) non-survived patients and 596 (57%) survived patients, were included. The most common comorbidity was diabetes mellitus (DM) (82.7%), chronic kidney disease (CKD) (43%), hypertension (25.7%), and obesity (23.6%). Our multivariate analysis indicated that older age (aOR: 1.03; 95%CI: 1.02–1.04, p<0.001), male sex (aOR: 1.29; 95%CI: 1.11–2.00, p=0.007), severe COVID-19 at first admission (aOR: 3.13; 95%CI: 2.08–4.73, p<0.001), having pneumonia (aOR: 1.99; 95%CI: 1.21–3.33, p=0.005), poorly controlled DM with HbA1c≥9% (aOR: 2.90; 95%CI: 1.72–4.89, p<0.001), severe obesity with body mass index (BMI)≥30 (OR: 2.90; 95%CI: 1.72–4.89, p<0.001), hypertension stage 2 (aOR: 1.99; 95%CI: 1.12–3.53, p=0.019) or stage 3 (aOR: 6.59; 95%CI: 2.39–18.17, p<0.001), CKD stage 3 (aOR: 2.50; 95%CI: 1.36–4.59, p=0.003), stage 4 (aOR: 5.47; 95%CI: 2.18–13.69, p<0.001) or stage 5 (aOR: 1.71; 95%CI: 1.04–2.81, p=0.036), and having chronic lung disease (aOR: 3.08; 95%CI: 1.22–7.77, p=0.017) significantly increased the risk of COVID-19 mortality. In contrast, COVID-19 vaccination reduced the risk of COVID-19-associated death. This study highlights that more severe comorbidities, advanced age, and incomplete vaccination were associated with COVID-19 mortality.